Cutaneous Vasodilation during Local Heating: Role of Local Cutaneous Thermosensation - Mack, Gary W.; Foote, Kristopher M.; Nelson, W. Bradley (Frontiers in Physiology, 2016)
We tested the hypothesis that cutaneous vasodilation during local skin heating in humans could be manipulated based upon the ability to desensitize TRPV4 ion channels by applying the thermal stimuli in a series of pulses. Each subject was instrumented with intradermal microdialysis probes in the dorsal forearm skin and perfused with 0.9% saline at 1.5 µl/min with local skin temperature controlled with a Peltier unit (9 cm2) at 34°C. Local skin temperature was manipulated for 50 min in two classic ways: a step increase to 38°C (0.1 °C/sec, n=10), and a step increase to 42°C (n=10). To desensitize TRPV4 ion channels local skin temperature was manipulated in the following way: pulsed increase to 38°C (1 pulse per min, 30 sec duration, 1.0°C/sec, n=10), and 4) pulsed increase to 42°C (1.0°C/sec, n=9). Skin blood flow (SkBF, laser Doppler) was recorded directly over the middle microdialysis probe and the dialysate from all three probes were collected during baseline (34°C) and each skin heating period. The overall cutaneous vascular conductance (CVC) response to local heating was estimated from the area under the % CVCmax-time curve. The appearance of the neuropeptide calciton gene related peptide (CGRP) in dialysate did not change with skin heating in any protocol. For the skin temperature challenge of 34 to 38°C, the area under the % CVCmax-time curve averaged 1196 ± 295 (SD) % CVCmax•min seen during the step change in skin temperature, which was larger than the 656 ± 282 % CVCmax•min during pulsed heating (p< 0.05). For the skin temperature challenge of 34 to 42°C, the area under the % CVCmax-time curve averaged 2678 ± 458 % CVCmax•min during the step change in skin temperature, which was larger than the 1954 ± 533 % CVCmax•min during pulsed heating (p< 0.05). The area under the % CVCmax•min curve, was directly proportional to the accumulated local skin thermal stress (in °C•min) (r2 = 0.67, p<0.05, n = 39). This association indicates a critical role of local integration of thermosensitive receptors in mediating the cutaneous vasodilator response to local skin heating. Given that we saw no differences in the levels